2011
DOI: 10.1186/cc10285
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of ventilator-associated pneumonia, mortality and all intensive care unit acquired infections by topically applied antimicrobial or antiseptic agents: a meta-analysis of randomized controlled trials in intensive care units

Abstract: IntroductionGiven the high morbidity and mortality attributable to ventilator-associated pneumonia (VAP) in intensive care unit (ICU) patients, prevention plays a key role in the management of patients undergoing mechanical ventilation. One of the candidate preventive interventions is the selective decontamination of the digestive or respiratory tract (SDRD) by topical antiseptic or antimicrobial agents. We performed a meta-analysis to investigate the effect of topical digestive or respiratory tract decontamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 91 publications
5
49
0
9
Order By: Relevance
“…These data are in agreement with the effects shown by others. [37][38][39] Although not critically ill and not usually requiring mechanical ventilation support for Ͼ 24 h, patients undergoing elective cardiac surgery are likely to develop VAP. For example, this study found a decreased incidence of VAP with oral hygiene and chlorhexidine gluconate oral rinses 72h before surgery and therefore before endotracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…These data are in agreement with the effects shown by others. [37][38][39] Although not critically ill and not usually requiring mechanical ventilation support for Ͼ 24 h, patients undergoing elective cardiac surgery are likely to develop VAP. For example, this study found a decreased incidence of VAP with oral hygiene and chlorhexidine gluconate oral rinses 72h before surgery and therefore before endotracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] The most important measures are continuous medical education, [16][17][18] continuous suctioning of subglottic secre-tions, 19 semi-recumbent position, 11,[20][21][22][23][24][25] oral hygiene with chlorhexidine, 26 and selective digestive decontamination. 6,[27][28][29][30][31] Knowledge of guidelines for prevention of VAP among healthcare workers (HCWs) has been infrequently assessed and mainly in staff nurses only. The gaps between individual knowledge of VAP prevention and actual daily clinical practice have not been compared.…”
Section: Introductionmentioning
confidence: 99%
“…This may be the reason why they are not commonly applied 2,3 , VAP infections in intensive care units are a phenomenon with a range of health issues. They are the reason behind prolonged hospitalisation, increased mortality and significant increase in treatment costs 4,5 . According to the literature, 20-50% of all hospital infections are developed in ICUs, with a significant portion of those consisting of VAP infections [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%